2006
DOI: 10.4070/kcj.2006.36.9.661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking and Smoking-Related Parameters on Acetylcholine-Induced Coronary Artery Spasm

Abstract: Background and Objectives:Smoking has been known to be an independent risk factor of the coronary morbidity induced by coronary artery endothelial dysfunction, but its detailed impact, including the duration and amount of smoking on coronary artery spasm, has not been clarified yet. We investigated the incidence of acetylcholine (Ach)-induced coronary artery spasm according to smoking and the smoking-related parameters. Subjects and Methods:The study consisted of 306 patients (163 males, age: 56.1±11.2 years),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The results of this study showed that male smokers remained the majority of patients with coronary spasm, while only about one-fifth of patients were females. Previous studies of coronary spasm, including those from Korea and Japan, showed that smoking was the most important risk factor of coronary spasm, while other traditional risk factors for obstructive coronary artery disease, such as cholesterol and triglyceride levels were not 6-10). In this study, female patients also had lower rates of a positive smoking history and they were younger than male patients.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The results of this study showed that male smokers remained the majority of patients with coronary spasm, while only about one-fifth of patients were females. Previous studies of coronary spasm, including those from Korea and Japan, showed that smoking was the most important risk factor of coronary spasm, while other traditional risk factors for obstructive coronary artery disease, such as cholesterol and triglyceride levels were not 6-10). In this study, female patients also had lower rates of a positive smoking history and they were younger than male patients.…”
Section: Discussionmentioning
confidence: 44%
“…Previous studies of coronary spasm, including those from Korea and Japan, showed that smoking was the most important risk factor of coronary spasm, while other traditional risk factors for obstructive coronary artery disease, such as cholesterol and triglyceride levels were not. 6 - 10) In this study, female patients also had lower rates of a positive smoking history and they were younger than male patients. The smoking rate in a general Korean female was also very low compared to that of a Korean male (4% vs. 52%).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“… 4) Due to its strong association with endothelial dysfunction, cigarette smoking is known to markedly increase the risk for all forms of cardiovascular diseases such as atherosclerosis, ACS, stroke, and CAS. 5) 6) 7) 8) 9) Thus, for CAS patients an intensive medical therapy and close clinical follow-up should be recommended. For CAS patients who smoke, the importance of smoking cessation should be emphasized in order to reduce the risk.…”
Section: Introductionmentioning
confidence: 99%
“…Sugiishi et al also reported that cardiovascular risk factors such as hypertension, hyperlipidemia, and diabetes did not show significant correlation with Ach-induced significant CAS [15]. Several studies reported that cigarette smoking [15][16][17] and alcoholic drinking [18,19] have significant correlations with CAS. Yasue et al summarized that CAS has been thought to occur at a site of organic stenosis of a major coronary artery [7].…”
Section: Discussionmentioning
confidence: 90%